Re-evaluation of mouse models of endometriosis for pathological and immunological research - He, Ying; Liang, Bo; Hung, Sze Wan; Zhang, Ruizhe; Xu, Hui; Chung, Jacqueline Pui Wah; Wang, Chi Chiu (Frontiers in Immunology, 2022)
Endometriosis is an estrogen-dependent gynecological disease with chronic pelvic in-flammation. In order to study pathophysiology of endometriosis and examine thera-peutic effects of new pharmaceuticals for endometriosis treatment, different animal models had been developed in the last two decades, especially mouse models. However no study evaluated effects of various modeling approaches on pathology and immu-nology in endometriosis. This study aimed to compare endometriotic lesion develop-ment and immune profiles under different methods of establishing endometriosis models in mice, including estrus synchronization (ovariectomy with estrogen supplement versus male urine-soaked transfer bedding), endometrium preparations (whole uterus including endometrium and myometrium fragments versus solely endometrium fragments), and surgical transplantation (subcutaneous transplantation versus intra-peritoneal injection). Our results showed that lesion growth under estrus synchroniza-tion by ovariectomy with estrogen supplement had higher success rate and more pro-liferative endometrium, apart from higher body weight gain. Immune response in pe-ripheral blood were similar in whole uterus and solely endometrium fragments and in intraperitoneal injection and subcutaneous transplantation, but more innate immune response in peritoneal microenvironment was found in solely endometrium fragments and intraperitoneal injection than counterparts. In conclusion, different endometriosis modelling methods result in different pathological and immunological features. Ovar-iectomy with estrogen supplement, solely endometrium fragments and intraperitoneal injection are more suitable for both pathological and immunological studies of endometriosis in mice, which are important for mechanistic studies and immunotherapy development.